Household Water Demand Estimation using Micro-Level Data - Marie-Estelle Binet; Stéphanie Durand; Michel Paul; Fabrizio Carlevaro (European Regional Science Association (ERSA), 2005)
La Reunion Island is facing to specific difficulties in supplying drinking water. In the western part of this french departement drincking water is lacking. In this context, well-suited policies require to know perfectly households consumption behavior. To this end, the household water demand function is estimated. Data have been recorded on a random sample of 2000 consumers by a telephone poll. Water bills have been collected by post, from 200 volunteer households.
Keywords: 330